An Interpretation of Late Quaternary Glacial Flow Indicators in the Baie des Chaleurs Region, Northern New Brunswick - Pronk, A.; Bobrowsky, P.; Parkhill, M. (Géographie physique et Quaternaire, 1989)
ABSTRACTA sequence of late Quaternary geologic events in northern New Brunswick is determined from striation analysis derived from published data, open file reports, and field research conducted by the authors since 1985. These data are integrated with clast provenance and clast fabric trend analysis, as well as information from other studies in the surrounding area. South of the Baie des Chaleurs, a complicated Late Wisconsinan glacial history is preserved in the form of erosive features including nailhead striae, miniature crag-and-tails, and various scars, striations, and fractures. The rarity of sedimentary deposits and datable materials precludes simple stratigraphie interpretation. Based on over 1,000 striation sites, we conclude four major phases of glacial flow affected the area during the Late Wisconsinan: 1) an early flow to the southeast which reflects local Appalachian ice; 2) a second phase of glacial flow to the east indicating a Laurentide ice influence in western New Brunswick; 3) a third phase of glacial flow to the north-northeast, which may represent ice response to drawdown in the Baie des Chaleurs; and 4) a final multidirectional flow indicating localized ice response during the last stages of Late Wisconsinan glaciation. The absence of Canadian Shield erratics in northern New Brunswick is explained in terms of ice streaming along the St. Lawrence channel beneath a southward-flowing Laurentide Ice Sheet. Basal ice debris (including Shield erratics) was apparently truncated and removed by the obliquely flowing ice stream, leaving relatively clean ice in the Ice Sheet as it entered Gaspésie and ultimately New Brunswick.